The researcher gap and regulations in the university system: an approximation for its calculation during the year 2021 in Peru (LACCEI, 2024)
Academic research is one of the engines of a country's development through its university system, and it is so important that for the granting of the first institutional license a minimum of 3% of researchers was required in relation to its teaching staff. The objective was to estimate the researcher-teacher gap in the public university system based on the data processed in the first licensing carried out by the National Superintendence of Higher Education SUNEDU. The quali-quantitative method of documentary review was used, and an equation was proposed to calculate the gap in each university with the parameters: number of teachers and students, whose variables are target rates that each university can set according to its strategic plans, programs and resources. The population was 6880 researchers qualified by the National Scientific Technological and Technological Innovation Registry RENACYT at the end of 2021 and the sample was 2314 researchers from the 46 licensed public universities. It is concluded that 29 universities (63%) would have a gap of 1637 researchers and that with the proposed model 80.4% of public universities would exceed the 5% ratio of RENACYTS researchers in the next licensing in Peru